Crucial moments in the chair experience: A case study approach - Shawn T. Wahl; Amy Aldridge Sanford; Chad McBride (Academic Chairpersons Conference Proceedings, 2016)
Department chairs are often called upon to make tough decisions (e.g., personnel, scheduling, strategic planning, curriculum, resources). Presenters of this interactive workshop will share case studies written by higher education administrators from across the nation, offer persepctives, and open it up for interaction, brainstorming and discussion for addressing difficult situations.
Keywords: Interactive workshop; case studies; leadership development; problem-solving; conflict management